2021
DOI: 10.18632/aging.203502
|View full text |Cite
|
Sign up to set email alerts
|

SLCO1B3 promotes colorectal cancer tumorigenesis and metastasis through STAT3

Abstract: Solute carrier organic anion transporter family member 1B3 (SLCO1B3) is a gene that encodes an organic anion-transporting polypeptide (OATP) 1B3, a membrane-bound multi-specific transporter in hepatocytes. SLCO1B3 was first reported in hepatocytes. Later, it was found that its expression is higher in colorectal cancer (CRC) than in the adjacent normal tissue. However, the role of SLCO1B3 in CRC is not well elucidated. In this study, the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It was found that Th17-type cytokines, IL-6 and TNF-α synergistically activate STAT3 to promote the growth of colorectal cancer cells [ 26 ]. SLCO1B3 can promote the proliferation and metastasis of colorectal cancer by activating the STAT3 pathway [ 27 ]. Previous studies have confirmed that the activation of STAT3 is related to the poor prognosis of tumors, including head and neck tumors, B-cell lymphoma, cervical cancer, gastric cancer, colon cancer, liver cancer, glioma and esophageal cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that Th17-type cytokines, IL-6 and TNF-α synergistically activate STAT3 to promote the growth of colorectal cancer cells [ 26 ]. SLCO1B3 can promote the proliferation and metastasis of colorectal cancer by activating the STAT3 pathway [ 27 ]. Previous studies have confirmed that the activation of STAT3 is related to the poor prognosis of tumors, including head and neck tumors, B-cell lymphoma, cervical cancer, gastric cancer, colon cancer, liver cancer, glioma and esophageal cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It transports several endogenous and exogenous compounds. SLCO1B3 contributes to the development of several cancers and regulates tumor sensitivity to chemotherapy [ 40 , 41 ]. Nonetheless, its expression and biological function in BLCA have never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…20 SLCO1B3 could be a novel carcinogen in colorectal cancer (CRC), which drives CRC tumor occur and metastasis. 21 In vivo tumor construction in non-small cell lung cancer cells is inhibited by cancer type-SLCO1B3 (Ct-SLCO1B3) knockdown. 22 As a tumor suppressor, CDX2 could inhibit Wnt/β-catenin signaling so that colon cancer cells cannot proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…SLCO1B3 could be a novel carcinogen in colorectal cancer (CRC), which drives CRC tumor occur and metastasis 21 . In vivo tumor construction in non‐small cell lung cancer cells is inhibited by cancer type‐SLCO1B3 (Ct‐SLCO1B3) knockdown 22 …”
Section: Discussionmentioning
confidence: 99%